ANALISIS PELAYANAN KESEHATAN BERBASIS PROGRAM BPJS DI KLINIK PRATAMA DAN APOTEK MULIA MEDIKA - Hamdan Hamdan; Widi Aulia Lestari (Economicus : Jurnal Ekonomi dan Manajemen, 2024)
This study aims to examine the services provided to BPJS patients in Cihampelas District, West Bandung Regency. The research uses a qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the healthcare services provided at Klinik Pratama and Apotek Mulia Medika for BPJS participants are quite good. Patients are satisfied with the quality of services provided, including administration, medication services, and the comfort of the waiting room. However, there are still some challenges related to participants' understanding of BPJS facilities and accessibility barriers. This study offers valuable insights into the quality of BPJS services at primary healthcare facilities and can serve as an evaluation tool for service improvement in the future.